PERANAN KOMITMEN PROFESI AKUNTAN DALAM MEMODERASI PENGARUH CLIENT IMPORTANCE PADA KUALITAS AUDIT - Devi, Sunitha; Dewi, Luh Gede Kusuma; Dewi, Putu Eka Dianita Marvilianti (Universitas Airlangga, 2019)
This research was done in purpose of finding out empirical evidences about the effects of client importance towards the audit quality, danthe commitment ability of the accounting profession in weakening the influence of client importance on audit quality. The research sample that returned the results of questionnaires is36 auditors from a total of 65 auditors working in the Public Accounting Firm (KAP) in 2018.The sample selection was done using the purposive sampling method. The data sources used in this study are primary data. Primary data is obtained by using a questionnaire that has been structured in order to collect information from the auditor as the respondent in this study. MRA model analysiswas applied to analyze the data. The data analysis support the hypothesis: (1)client importance has negative insignificant effect towards the audit quality, dan(2) commitment of the accounting profession was able to moderatethe influence of client importance on audit quality. The results of this study can be used as reference material for KAP leaders in evaluating danperforming more strict supervision on the implementation of professional commitment of auditors when conducting audit process, because the existence of KAP depends on the quality of audits that can affect public trust. Regulators can also make very strict rules dansanctions related to violations of the accounting code of ethics danviolations of the audit process so that they can cause deterrent effects for the perpetrators dancan be used as learning for other auditors so as not to violate these rules